IMPLEMENTASI NILAI-NILAI PENDIDIKAN KARAKTER DALAM PEMBENTUKAN AKHLAK PADA SISWA SDN TANJUNG SARI 02 - Siti Muflihah; Tajuddin Noor; Undang Ruslan Wahyudin (Universitas Pakuan, 2021)
IMPLEMENTATION OF CHARACTER EDUCATION VALUES IN THE FORMATION OF MORALS IN TANJUNG SARI 02 ELEMENTARY SCHOOL STUDENTS This article aims to capture the implementation of character education values in the formation of morals in elementary school students. The inculcation of ethical values and good character has been the government's concern lately, to stem the flow of globalization and technological advances which, if not directed and addressed wisely, will turn into things that are very dangerous and have an impact on students' moral morality. The problems in the world of education in Indonesia in its development have given rise to new problems related to students, teachers, curriculum, and policies from the government itself, which are considered to have not found the right and effective formula for the realization of a well-integrated education system. This research uses qualitative research methods, with descriptive analysis. The approach used is using a normative theological approach, a pedagogical approach, and a psychological approach. The location of the research was conducted at SD Negeri Tanjung Sari 02, Cikarang Utara District, Bekasi Regency. Data were taken from the principal, teachers, and students using interview, observation, and documentation techniques. The findings show that the values of character education instilled in this school are religious, discipline, tolerance, perseverance, curiosity, care, honesty, and responsibility. In practice, teachers try to familiarize students with shaking hands and saying greetings when meeting friends, teachers, and employees; Do tadarrusan before learning begins; Carrying out dhuha prayers in congregation in the school field; pesantren kilat in the month of Ramadan; Carry out the observances of Islamic holidays. The results of the implementation of the values of character education show an increase in students in the form of a solid personality, high moral integrity, and noble morals.